Serological evidence of Midichloria mitochondrii circulation in humans parasitized by I. ricinus in Germany and development of a marker for tick bite (International Journal of Health, Animal Science and Food Safety, 2017)
The tick Ixodes ricinus transmits several microorganisms of medical and veterinary importance. Midichloria mitochondrii (order Rickettsiales; family Midichloriaceae) is an intracellular symbiont present in the ovaries and salivary glands of 100% of adult I. ricinus females (Sassera et al., 2008) and is transmitted to the vertebrate host during the tick bite (Mariconti et al., 2012; Bazzocchi et al., 2013) despite its infective role is not demonstrated.In this experimental study, a total of 324 human from different areas of Germany were analysed in order to investigate the seropositivity against the flagellar FliD protein of M. mitochondrii using an ELISA approach. Fifty sera were collected from patients living in non-endemic areas and used as negative controls while 274 sera were obtained from subjects exposed to tick bite and suffering from several symptoms referred to tick borne diseases and collected at the BCA clinic in Augsburg.Since the positivity for the spirochete Borrelia burgdorferi transmitted by I. ricinus is indicative for the tick bite, we considered also this additional information.The obtained results showed that 82 out of 274 sera were positive to M. mitochondrii and 42 out of 175 sera of subjects negative to B. burgdorferi were positive to M. mitochondrii to confirm the good property of FliD protein as a tick bite marker. However, the high number (133 out of 274) of subjects parasitized by I. ricinus but negative to both bacteria prompted us to detect new more suitable I. ricinus/M. mitochondrii antigenic proteins to use as markers for tick bite. For this purpose, three I. ricinus proteins and one surface protein of M. mitochondrii were selected and 12 synthetic peptides were designed in order to set-up a new ELISA test for investigating the exposure of humans and animals to this tick species.
Keywords: Ixodes ricinus; Midichloria mitochondrii; Serological markers; Tick bite